A new method of multi-scale fracture identification in tight gas sandstone reservoir. Issue 2 (4th March 2019) - Wu, Tao; Wang, Yuezhi; Fu, Bin; Wu, Peng
ABSTRACT: Identification of fractures is an important guide for the selection of well location as well as improvement of single-well recovery. In this paper, large-scale fractures of Su 48 block (target well) located in Sulige gas field were predicted using the coherence, curvature and anti-tracking analysis while small-fractures prediction were performed using R/S fractal statistical method. The observations revealed that, development of large-scale fractures were not that significant, whilst those of a smaller scale were distributed across the near-wellbore formation constituted of mudstone. Moreover, predicted results using the multi-scale fusion fracture developed model showed good agreement of the existence of fractures during horizontal well drilling in real time. Furthermore, the predicted fractures matched well with those observed in the field. Hence, reflecting the significance of tight gas sandstone reservoir fracture identification method.